The Impact of Halal Tourism on Regional Economic Growth in Lombok, West Nusa Tenggara, Indonesia - Lalu Hendra Wijaya; Maimun Sholeh (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2020)
Abstract. This study aims to analyze the economic development of the West Nusa Tenggara Province with the existence of halal tourism. It is expected that the halal tourism is able to support the economic development of the province. This is a quantitative research, u sing secondary data from the Central Statistics Agency (BPS) among others. The analysis tool used is SPSS. The results show that halal tourism has considerable potential as one of the leading sectors that can support the regional economy. The progress of the tourism sector in the West Nusa Tenggara Province is marked by the increase in the number of foreign and domestic tourist visits every year.Keywords: Economic Growth, Halal Tourism, West Nusa Tenggara Abstrak. Penelitian ini bertujuan untuk mengetahui perkembangan atau pertumbuhan ekonomi Provinsi Nusa Tenggara Barat dengan adanya pariwisata halal sehingga mampu menopang perekonomian regional provinsi. Penelitian ini menggunakan pendekatan kuantitatif, dengan data sekunder yang di antaraya berasal dari Badan Pusat Statistik (BPS). Alat analisis yang digunakan adalah SPSS. Hasil penelitian menunjukkan bahwa Pariwisata halal memiliki potensi yang cukup besar sebagai salah satu sektor unggulan yang dapat menopang ekonomi daerah. Kemajuan sektor pariwisata di Provinsi NTB ditandai dengan meningkatnya angka kunjungan wisatawan mancanegara dan nusantara setiap tahunnya.Kata kunci: Pertumbuhan Ekonomi, Wisata Halal, Nusa Tenggara Barat